2017
DOI: 10.1186/s12995-017-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals effect on breast cancer progression

Abstract: BackgroundBreast cancer is the most frequent localization of malignant process in American women and women of European countries. To date it is not possible to control the morbidity growth due to lack of effective ways of primary prevention. Comparing the incidence of breast cancer in developed countries with the countries of Asia and Africa, there is the fact of population predominance lesion in more urbanized countries. This suggests that the environment along with other factors, occupies a significant place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 26 publications
3
39
0
7
Order By: Relevance
“…Instead, other studies suggest that accumulation of aluminium in diseased tissue could be the result rather than the cause for cancer development (Mirick et al 2002;Ogoshi et al 1994). This hypothesis is further strengthened by the findings of other studies that the amount of other elements, such as iron, nickel, chromium and lead, is also significantly elevated in breast cancer tissue (Ionescu et al 2007;Romaniuk et al 2017). However, one recent study indicates the respective aluminium to at least partly originate from the use of antiperspirants (Lenhart et al 2017).…”
Section: Genotoxicity and Carcinogenicitymentioning
confidence: 88%
“…Instead, other studies suggest that accumulation of aluminium in diseased tissue could be the result rather than the cause for cancer development (Mirick et al 2002;Ogoshi et al 1994). This hypothesis is further strengthened by the findings of other studies that the amount of other elements, such as iron, nickel, chromium and lead, is also significantly elevated in breast cancer tissue (Ionescu et al 2007;Romaniuk et al 2017). However, one recent study indicates the respective aluminium to at least partly originate from the use of antiperspirants (Lenhart et al 2017).…”
Section: Genotoxicity and Carcinogenicitymentioning
confidence: 88%
“…Therefore, soil, water and nutrition of Rafsanjan and the adjacent townships, located the North-West of the province, are subject to the potential negative effects of these heavy metals. Indeed, previous studies have found associations between heavy metals and breast and prostate cancers (50)(51)(52). The current study strongly recommends to examine the hypothesis which exposure to heavy metals, especially arsenic and copper, may associate with high incidence of gender-speci c cancers in the northwest of Kerman Province.…”
Section: Resultsmentioning
confidence: 85%
“…Nevertheless, more recent research has shown that the that long-term of HMS exposure leads to increases of HM accumulation level in the UB tissue which influence significantly on the morphometric parameters of organ wall thickness (this data has not been published yet).A lot of simulated studies demonstrated that the organ easily exposed to development of inflammatory diseases of various genesis that accompanied by urodynamic disorders 15,17 . A considerable amount of scientific data on associate disruption of the level of physiological concentrations trace elements with the development of oncological pathology of the bladder and other different organshas been published 9,10,[19][20][21] . Taking into account, the technological development of the industry and the use of chemical fertilizers in agriculture led to environment pollution by HM 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the imbalance in chemical elements leads to the homeostasis disruption and the development of the pathologies, caused by the effect of these pollutants 3,6,8 . More recently, new information appears in the world literature that describes the pathogenetic features of the development of environmentally caused diseases due to the residence in contaminated areas 8,10 . Uncontrolled growth of the rate of HMS is mostly accompanied by the failure of the compensatory mechanisms of the body with the development of oxidative stress due to the imbalance between the active oxygen species and antioxidants 11 .…”
Section: Introductionmentioning
confidence: 99%